FASAKH NIKAH DENGAN ALASAN SUAMI MISKIN (Studi Perbandingan antara Ulama Syafi’iyyah dan Hukum Positif di Indonesia) - Muhammad Habibi; Syahrizal Abbas; Sitti Mawar (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
In a family sometimes painful actions arise from involuntary causes (not intentionally), not on the wishes of the husband, such as because the husband is poor or poor so he does not have a living to fulfill his wife's rights in the form of food, clothing and home at a certain time, which makes the wife ask to part with her husband through the divorce (fasakh) path. Regarding the problem of the wife asking for fasakh (carrying out divorce) by reason of a poor husband there are differences of opinion between the Syafi'iyyah Ulama and Positive Law in Indonesia concerning the provisions that must be fulfilled by both. This study wants to answer the question of how the provisions of fasakh marriage are based on the reasons of poor husbands according to Syafi'iyyah Ulama and Positive Law in Indonesia. To get answers, the author uses primary data sources and secondary data. The research method that I use is Descriptive Comparative method that is research by analyzing and comparing opinions, reasons and interpretations of the arguments used as the opinions of the two groups. The results of the study indicate that the fasakh of marriage on the grounds of a poor husband according to the Shafi'iyyah Ulama is permissible and validly carried out on condition; 1) A wife who is married between being patient and divorced, 2) Judge's decision, in the form of; a. determination of poor status according to the provisions, b. giving an opportunity to a husband to work for a living, c. Fasakh implementation period three days after the wife reported. 3) Separated by reciting fasakh instead of divorce, and still having three times the right of divorce if in the future you want to remarry with a new contract. Whereas according to Positive Law in Indonesia fasakh marriage by reason of poor and permissible husband with conditions, 1) occur shikak between wife and husband, 2) wife make a divorce letter, 3) Decision judge namely proof of poor husband in a literal manner, 4) Court decision drop one bain sughra talak. From the explanation above, it can be concluded that the provisions of the fasakh of marriage by reason of poor husbands in the opinion of the Syafi'iyyah clerics are better and fair because they are supported by a strong foundation and are most in accordance with the soul, basis and principles of Islamic law. Therefore in Indonesia requires more explicit rules about fasakh (divorce) with the excuse of poor husbands.